Value of baseline clinical and CMR characteristics for the prediction of cancer therapeutics-related cardiac dysfunction: results from the Cardiotoxicity Prevention Research Initiative (CAPRI). (25th November 2020) - Labib, D; Dykstra, S; Slavikova, Z; Feuchter, P; Rivest, S; Flewitt, J; Howarth, A; Heydari, B; Lydell, C; Clarke, B; Kolman, L; Pituskin, E; et al.
Abstract: Background: Whether baseline cardiovascular health status significantly influences the risk of Cancer Therapeutics-Related Cardiac Dysfunction (CTRCD) in patients receiving de-novo chemotherapy exposure is an important clinical question for both surveillance and management decisions. The reference standard technique for the serial monitoring of left ventricular (LV) volumes and ejection fraction (EF) is cardiovascular magnetic resonance (CMR). Using this technique, we sought to prospectively evaluate baseline clinical risk factors and CMR-based pre-exposure characteristics for their influence on the incident occurrence of CTRCD. Methods: We prospectively enrolled 371 cancer patients referred for baseline (pre-chemotherapy) followed by surveillance CMR imaging as part of the Cardiotoxicity Prevention Research Initiative (CAPRI). We also recruited 62 healthy volunteers to evaluate for referral population differences in CMR-based markers. Study subjects and healthy volunteers underwent identical CMR imaging protocols inclusive of cine imaging, T1 and T2 mapping. CTRCD was defined according to surveillance CMR imaging with criteria established as a drop in LVEF by >5% (meaningful detectable difference for CMR technique) to a value ≤56% (lower limit of normal) at any time point during chemotherapy surveillance. A total of 1474 CMR studies were performed over a median surveillance period of 12.5 months (range 2.3 to 68.9 months). Results: The majority of patients were female (77%), being referred for breast cancer (64%) or lymphoma (36%), with a mean age of 54.0±14 years. The baseline prevalence of hypertension, diabetes, hyperlipidemia, and current smoking were 32%, 11%, 46%, and 13%, respectively. Compared to healthy volunteers, cancer patients at baseline showed smaller indexed LV and RV volumes, higher indexed LV mass, and higher native T1 values (mean difference +33 msec; p<0.001). LV and right ventricular (RV) EF and T2 mapping values were not significantly different. CTRCD criteria were met in 22% of patients. Figure 1 shows a forest plot of univariable and multivariable predictors of CTRCD occurrence. Following multivariable adjustment, only combined anthracycline/trastuzumab regimen (OR 4.4, 95% CI 2.0–9.5) and baseline indexed LVEDV (OR 2.3, 95% CI 1.2–4.5) were found to be significant predictors of this outcome. Conclusion: Using the reference standard of serial CMR imaging we identified that of all baseline (pre-chemotherapy) clinical and CMR-based markers of cardiovascular health, only indexed LV end-doastolic volume (EDV) was independently associated with future occurrence of CTRCD following adjustment for chemotherapy regimen. We did not observe significant associations with conventional cardiac risk factors in our study population. The observed risk for indexed LVEDV was clinically meaningful (2.3-fold risk per 10 ml/m 2 ) and warrants further investigation as a relevant baseline marker of risk in this referral population. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Alberta Innovates/Genome Alberta: CAPRI